A novel approach for RFID based distributed security against physical access of university data. Issue 8 (17th November 2019) - Sengupta, Savio Jay; Biswas, Bikram; Sen, Dipanjan; Ray, Sudhabindu; Roy, Subhashis; Sarkar, Subir Kumar
Abstract: A customized distributed security system has been designed by using RFID to achieve a reliable high-end communication system for universities. In this work, an overview of the existing problems related to distributed security has been introduced first and then the proposed systems are designed using RFID in detail. The problems related to security breeching in the universities are very common. A detailed study has been done considering the security breaching and access in case of the universities. Keeping in mind the present scenario of high-end securities for the corporate industries, banks etc., we have designed a distributed security system using Low frequency RFID technology for universities. The system has been practically implemented in laboratory, and the experimental data shows that this system can be used widely in the universities efficiently to maintain the confidentiality